Pengaruh Kecukupan Modal dan Pembiayaan Bermasalah Terhadap Profitabilitas Bank Umum Syariah di Indonesia - Tampubolon, Arsyaf; Amin Hou; Debora Tambunan; Aminatu Zahra (Jurnal Mahkota Bisnis (Makbis), 2024)
This research aims to determine the influence of capital adequacy (CAR), non-performing financing (NPF) variables on profitability performance (ROA) in Sharia Commercial Banks in Indonesia for the period from 2015 to 2023. The type of data used in this research is quantitative data. The data source in this research is secondary data. The data collection technique was carried out using documentation techniques and data analysis using multiple linear analysis using the F test and t test at a significant level of 5% and the Adjusted R Square coefficient of determination was 87.43%. Changes in the ROA (Y) variable were explained by changes in CAR and NPF while the remaining 12.57% is explained by other variables not included in this study. Partial research results show that CAR and NPF have a significant effect on ROA. Simultaneous research results show that CAR and NPF have an effect on ROA.